Influence of Advertising Appeals in Hotel Industry: Role of Emotional, Rational, Endorsement and Aesthetic Appeals (PUSA Journal of Hospitality and Applied Sciences, 2025)
Background: The hospitality industry operates under highly competitive environment, where marketing and adverts  influence the decisions of consumers significantly. Emotional, rational, endorsement, and aesthetic advertising  appeals: the essential selling strategies to capture and draw in customers. Nevertheless, how far does either type of  appeal affects consumers in the hospitality domain is largely unexplored and should be administrated empirically.  Objective: The study had two major objectives. First, examining the influence of “social media advertising appeals  (emotional, functional, endorsement, and aesthetic) on” consumer buying behaviour with respect to hotel industry, and  second, to examine the relative strength of identified social media advertising appeals (emotional, functional, endorsement  and aesthetic) with respect to consumer buying behaviour in hotel industry. Methodology: “This study was exploratory  cum descriptive in nature.” Responses were collected from residents of Raipur, capital city of Chhattisgarh; having age  of 18 years or above, who had exposure to hotel advertisement or hotel services. This study employed convenience  sampling method to obtain response from the 337 respondents. SPSS 21.0 was used for the analysis; “multiple regression  was utilized to test the hypothesis and exploratory factor analysis (EFA) was used to extract the factors”. Results: The  study extracted four factors emotional appeal, rational appeal, endorsement appeal, aesthetic appeal, on admissible  range of Eigen values contributing 83.03% of total variance that contributes to consumer behaviour towards advertising  appeals in hotel industry. The multiple regression analysis revealed that rational appeal is strongly correlated (strongest  relationship) serving as one of the primary antecedents of consumer behaviour towards advertising appeals in hotel  industry followed by aesthetic appeal, emotional appeal, and endorsement appeal significantly with model explaining  substantial proportion of variance (0.64) in purchase decisions. Conclusion: “The findings of the study show that  emotional, rational,” endorsement, and aesthetic appeals affect consumer decisions of the hotel industry with the highest  impact made by emotional appeal. Hotels should focus more on storytelling and advertisements with visuals to enhance  engagement. This study provides strategic framework for marketers to create the most effective ads and convert actions  on bookings. We encourage future work to investigate whether the effectiveness of appeals differs by culture.
Keywords: Social media; advertising appeals; consumer buying behaviour; hotel industry; decision-making